2013
DOI: 10.1096/fj.12-217984
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signaling controls the expression of O ‐GlcNAc transferase and its interaction with lipid microdomains

Abstract: Lipid microdomains (rafts) are cholesterol-enriched dynamic ordered lipid domains belonging to cell membranes involved in diverse cellular functions, including signal transduction, membrane trafficking, and infection. Many studies have reported relationships between insulin signaling and lipid rafts. Likewise, links between insulin signaling and O-GlcNAcylation have also been described. However, the potential connection between O-GlcNAc and raft dynamics remains unexplored. Here we show that O-GlcNAc and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…Embryonic lethality and developmental delay observed by genetic deletion of Ogt or Mgea5 demonstrates the critical role of these enzymes in O-GlcNAc cycling (10,11). We (1), along with others (12)(13)(14), have observed alterations in the expression level of OGT and OGA protein along with concomitant protein O-GlcNAc modification in various pathological conditions. We recently reported that the up-regulation of miR-539 could be a mechanism for decreased OGA level in the infarcted mouse heart (15).…”
Section: The Posttranslational O-linked N-acetylglucosamine (O-mentioning
confidence: 87%
“…Embryonic lethality and developmental delay observed by genetic deletion of Ogt or Mgea5 demonstrates the critical role of these enzymes in O-GlcNAc cycling (10,11). We (1), along with others (12)(13)(14), have observed alterations in the expression level of OGT and OGA protein along with concomitant protein O-GlcNAc modification in various pathological conditions. We recently reported that the up-regulation of miR-539 could be a mechanism for decreased OGA level in the infarcted mouse heart (15).…”
Section: The Posttranslational O-linked N-acetylglucosamine (O-mentioning
confidence: 87%
“…Specifically, insulin signalling has been shown to regulate OGT through several distinct mechanisms, including modulation of OGT expression, subcellular localization, and enzymatic activity. In addition to upregulating OGT expression through a PI3K-dependent pathway, insulin stimulation promotes translocation of OGT from the nucleus to the cytoplasm and localization of OGT to lipid rafts in the plasma membrane, where it is activated via tyrosine phosphorylation by the insulin receptor 5, 87, 88 (Fig. 3c).…”
Section: Nutritional and Hormonal Regulationmentioning
confidence: 99%
“…Notably, reduced O-GlcNAcylation of Sp1 down-regulates the transcription of the pro-angiogenic factor VEGF-A (vascular endothelial growth factor A), involved in retinal vascularization [29]. Inhibition of OGT by Ac 4 -5S-GlcNAc provided insights into the role of OGT in the insulin response, showing a concerted role of O-GlcNAc and insulin-dependent signalling cascades on membrane lipid microdomains [30]. The compound has also been used on pancreatic cancer cells suggesting a correlation between hyper-O-GlcNAcylation and apoptosis via the modulation of the NF-κB antiapoptotic transcriptional activity [31].…”
Section: Substrate Analoguesmentioning
confidence: 99%